Why are we in an energy crisis?. Issue 6 (15th December 2022) - Abram, Simone
Abstract : Prices on international markets have rocketed recently. Domestic energy bills have gone up, possibly several‐fold, but so also have costs to manufacturers, hauliers, producers and everyone else. It appears to have been a revelation for some people to discover how thoroughly energy costs saturate everyday life from the personal to the general scale, shaping and shaped by international relations. Talking about this situation as an energy crisis has particular effects, from creating awareness of energy as a very odd kind of circulating matter to recognizing the infrastructures that tie people together and keep them apart. It also shows how vital it is that the anthropologies of energy have flourished in recent years, helping to highlight the ethical and moral dimensions of multiple energy infrastructures and their reach into everyday life around the world, whether there are grids or not.